Dropwise Condensation: Sprayable Thin and Robust Carbon Nanofiber Composite Coating for Extreme Jumping Dropwise Condensation Performance (Adv. Mater. Interfaces 1/2021). Issue 1 (12th January 2021) - Donati, Matteo; Lam, Cheuk Wing Edmond; Milionis, Athanasios; Sharma, Chander Shekhar; Tripathy, Abinash; Zendeli, Armend; Poulikakos, Dimos
Abstract : A polytetrafluoroethylene‐carbon nanofiber nanocomposite coating is applied on a copper substrate with an aluminum primer for superhydrophobicity to facilitate jumping dropwise condensation. While being durable and scalable, the coating delivers extreme heat transfer improvements up to ≈900%. More details can be found in article number 2001176 by Dimos Poulikakos and co‐workers.